PEMANFAATAN KATALIS SILIKA ALUMINA DARI BAGASSE PADA PEMBUATAN BIODIESEL DARI MINYAK GORENG SISA PAKAI - Sriatun, Taslimah dan Linda Suyati TIP (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
It was synthesized biodiesel from the used cooking oil using silica alumina catalyst. The aim of this research was to establish the catalytic performance in the form of silica alumina. The silica in sugarcane baggase was extracted by 6 M sodium hydroxide until sodium silicate was obtained. Synthesis of silica alumina catalyst was conducted by reaching sodium silicate with sodium aluminate, whereas the ratio was 1:1 (v/v), then the mixture was hydrothermaly heated at 100oC for 3 days. Catalytic ability was tested on transesterification reaction of used cooking oil and methanol. This catalytic test was to measure the performance of 1% silica alumina in converting used cooking oil into biodiesel. The variables were examined including ratios of methanol:used cooking oil (1:3, 1:6 and 6:1) and contact times (60 and 120 minutes). Catalyst characteristics were determined by XRD, FTIR, SEM-EDX and surface analyzer, meanwhile biodiesel as the product of transesterification was determined by GC-MS. The result showed that the silica alumina catalyst was Na-sodalite that had composition of Na 17.96%, Al 18.97% and Si 17.04%. Na-sodalite had homogenized shapes and sizes which the pore diameter of 4.55 Ao, pore volume of 5.73.10-3cc/g and surface area of 1.457.105cm2/g. The biodiesel obtained at methanol:used cooking oil of 1:3 for 60 minutes was 13.83% consisting of methyl caprylate, methyl caprate, methyl laurate, methyl myristate, methyl palmitate, methyl linoleat and methyl stearate. Whilst at methanol:used cooking oil of 6:1 yielded 85.51% biodiesel with methyl caprate as main component.Keywords:silica alumina, sugar cane bagasse, used cooking oil,biodiesel